Establishment of the menthol test as a clinical evaluation method for oxaliplatin-induced neuropathy - Yeongcheol Cheong; Hidetoshi Katsuno; Hiroshi Matsuoka; Masahiro Mizuno; Tomoyoshi Endo; Tadahiro Kamiya; Yosuke Tajima; Keigo Ashida; Yoshikazu Koide; Koji Masumori; Harunobu Sato; Tsunekazu Hanai; et al. (Fujita Medical Journal, 2022)
Objectives: To determine whether the tongue menthol test, which measures the cold sensation detection threshold (CDT) of the tongue, used before and after oxaliplatin administration is an objective evaluation method for oxaliplatin-induced peripheral neuropathy (OPN).